The Growth and Survival of Gouramy at Different Stocking Densities - Elvi Esa; Rusliadi Rusliadi; Iskandar Putra (Jurnal Akuakultur SEBATIN, 2024)
This study aims to determine the effect of different stocking densities on the growth and survival of gouramy (Osphorenemus gouramy) fed a feed containing booster aquaenzymes and to determine the best stocking density to increase growth and survival of gouramy. This research was conducted in November-January 2022 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The container used was an aquarium with a size of 30x50x50 cm. This study used a one-factor Completely Randomized Design (CRD) method with four treatments and three replications. The treatment levels applied in this study were P1 = stocking density of 10 gourami fish/30 L, P2 = 12 fish/30 L, P3 = 14 fish/30 L and P4 = 16 fish/30 L. The results showed that there was an effect of different stocking densities on the growth and survival of gouramy. The stocking density of 10 fish/30 L gave the best growth and survival performance, namely absolute weight growth of 4.06 grams, absolute length growth of 3.25 cm, specific growth rate of 1.93%, feed efficiency 42.69% and survival rate is 96.67%. The range of water quality during maintenance is in the tolerable range for the growth of gouramy fry, namely temperatures ranging from 26.7-28.4oC, pH 6.9-7.5, DO 5.2-5.9 mg/L, and ammonia 0.00047-0.00059 mg/L.